Optymalizacje podatkowe jako przykład strategii podatkowych - Bernaziuk, Anna (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
Tax restructuring (i.e. tax optimization) is based on analyzing assets of a company and identifying possible methods of classifying of these asset as tax deductible costs. The main goal of this classification is to reduce or entirely eliminate the tax liability. In the presented case the optimization is effectively a reduction of the tax liability by identifying assets and liabilities for tax effectiveness purposes. This presentation includes tax optimizations method applied in practice and based on empiric data. The process is based on the identification of a trade mark and subsequent contribution of the trade mark to a special purpose vehicle (SPV) which is set up as a partnership. Subsequently, the SPV charges the contributor with the resulting trade mark license fees and as a result the SPV is entitled to amortize the cost of the trade mark for tax purposes (reducing the tax liability).